Constraints in Adoption of Mushroom Production Enterprise (Indian Journal of Extension Education, 2014)
This study was an attempt to get the response regarding constraints faced by the respondents in adoption of mushroom production enterprise in Haidargarh block of Barabanki district. The sample for the study comprised of 50 randomly selected respondents trained by KVK in mushroom cultivation. The structured schedule was developed for data collection. Study revealed that ’lack of proper marketing channel’ was the most important constraint responsible for low rate of adoption. ’Distantly located markets’ and ’lack of government support’ were the other major obstacles in this process. ’Non availability of quality spawns’ & ’risk involve due to perishable nature’ were also observed as constraints by the mushroom growers.